Race matters in criminology: Introduction to the Special Issue. (August 2020) - Parmar, Alpa; Earle, Rod; Phillips, Coretta
As race scholars and criminologists we are attuned to Du Bois's (2007: 106) still meaningful injunction to 'oppose this national racket of railroading to jails and chain gangs the poor, the friendless and the Black'. Yet we have become concerned that criminology seems rather inured to the long-standing and deeply entrenched patterns of race and criminal justice which characterize many high-income countries, and certainly England and Wales and Australia, which are the geographical focus of this Special Issue of Theoretical Criminology .